Effects of spent mushroom substrates and inorganic fertilizer on the characteristics of a calcareous clayey‐loam soil and lettuce production. (11th November 2016) - Paredes, C.; Medina, E.; Bustamante, M. A.; Moral, R.
Abstract: We evaluated the effects of the addition of two types of spent mushroom substrate (SMS), SMS from an Agaricus bisporus crop (SMS1) and a mixture of SMSs from an A. bisporus crop and a Pleurotus crop (50% v/v each) (SMS2), on the characteristics of a calcareous clayey‐loam soil and the yield and nutritional status of lettuce ( Lactuca sativa L.), relative to crops receiving mineral fertilizer (M) and a control (C) without amendment. The application of SMS, especially SMS1, improved soil fertility compared with C and M soils. Moreover, the use of these organic substrates as soil amendments did not harm the plants and gave yields similar to that obtained with mineral fertilizer. The nutritional contents of the lettuce plants were greater than or similar to those of the plants from treatment C or M, except for the plant tissue concentrations of K, Fe and Zn, which were significantly reduced by SMS application. However, this latter fact did not reduce the lettuce yield in the amended soils. Therefore, the use of SMSs as organic amendments contributes to residue utilization, in an environmentally friendly way, and to improved soil fertility and crop yield.